2017
DOI: 10.1590/1980-5497201700020010
|View full text |Cite
|
Sign up to set email alerts
|

Tendências da autoavaliação de saúde em relação ao excesso de peso na população adulta residente nas capitais do Centro-Oeste do Brasil

Abstract: ABSTRACT:Objective: To estimate the trends of self-rated health in relation to overweight in the adult population of the capitals of the Brazilian Midwest region and the Federal District. Methods: Cross-sectional study with a population aged 20 to 59 years, using data from the Telephone-based Surveillance of Risk and Protective Factors for Chronic Diseases (VIGITEL), performed between 2008 and 2014. The estimates using the complex sampling design were made using simple linear regression, trend graphs and Boxpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
1
0
1
Order By: Relevance
“…Observou-se que os idosos com percepção de saúde ruim apresentaram razão de chance de 0,31 para o estado nutricional normal. Ressalta-se que a autoavaliação de saúde é um importante indicador de saúde global e os inquéritos populacionais ao longo das duas últimas décadas demostram a relação dessa variável com morbidades, mortalidade, fatores socioeconômicos e comportamentais entre a população idosa 23 . De fato, esse é um bom indicativo na velhice, como foi demonstrado no estudo de Maseda et al 24 realizado com 749 idosos espanhóis residentes na comunidade; os autores observaram que a autopercepção de saúde ruim esteve relacionada com desnutrição ou risco de desnutrição.…”
Section: Discussionunclassified
“…Observou-se que os idosos com percepção de saúde ruim apresentaram razão de chance de 0,31 para o estado nutricional normal. Ressalta-se que a autoavaliação de saúde é um importante indicador de saúde global e os inquéritos populacionais ao longo das duas últimas décadas demostram a relação dessa variável com morbidades, mortalidade, fatores socioeconômicos e comportamentais entre a população idosa 23 . De fato, esse é um bom indicativo na velhice, como foi demonstrado no estudo de Maseda et al 24 realizado com 749 idosos espanhóis residentes na comunidade; os autores observaram que a autopercepção de saúde ruim esteve relacionada com desnutrição ou risco de desnutrição.…”
Section: Discussionunclassified
“…Obesity is a public health concern in Brazil; which prevalence has been increasing over the years [7]. Some research has shown that high values of body mass index (BMI) and waist circumference (WC) are associated with poor self-rated health [810]. Moreover, social stratification has been considered a potential explanation for differences in health [11].…”
Section: Introductionmentioning
confidence: 99%